(untitled) (Marketing Journal, 2025)
In the evolving digital retail landscape, consumers increasingly demand personalized experiences. This study explores how SI -driven retail interfaces influence user engagement and the formation of purchase intentions. A hybrid SEM -AHP framework is employe d to analyze behavioral pathways shaped by algorithmic recommendations and adaptive interactions. The findings indicate that preference alignment, interface satisfaction, and behavioral consistency significantly affect decision confidence and purchasing te ndencies. The research emphasizes the strategic role of SI in enhancing consumer trust and minimizing uncertainty within omnichannel environments. These insights contribute to both theoretical understanding and practical implementation of SI -enhanced ret ail marketing strategies, especially in designing interfaces that align with dynamic consumer expectations.